PELATIHAN PEMANFAATAN GOOGLE BUSINESS PROFILE UNTUK MENINGKATKAN STRATEGI DIGITAL MARKETING BAGI PELAKU UMKM DI KELURAHAN KEDUNG BARUK, KOTA SURABAYA - Nugroho, Novianto Eko; Djawoto; Anton Eko Yulianto; Dian Arini (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
Digital transformation is a crucial factor for the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in facing increasingly competitive market challenges, yet many entrepreneurs in Kedung Baruk Village still encounter obstacles in optimizing digital platforms. This community service initiative aims to empower MSME actors through the utilization of Google Business features as a strategic digital marketing instrument to enhance online visibility, credibility, and market reach. The implementation method employed a participatory approach, encompassing stages of problem identification, socialization on the urgency of digital marketing, technical training on business profile management, as well as intensive mentoring and periodic evaluation. The results of the activity indicate a significant improvement in the partners' digital skills, as participants are now capable of independently managing account profiles, optimizing product catalog features, and analyzing consumer search trends through Google Business Insights. The integration of Google Business with other social media channels has proven to strengthen brand identity and facilitate direct interaction with potential customers. The conclusion of this program emphasizes that continuous technological assistance is essential for MSMEs to enhance local economic competitiveness and build consumer trust in a dynamic digital transformation era.